1‐(Azidomethyl)‐5H‐Tetrazole: A Powerful New Ligand for Highly Energetic Coordination Compounds. Issue 38 (25th May 2022) - Kofen, Moritz; Lommel, Marcus; Wurzenberger, Maximilian H. H.; Klapötke, Thomas M.; Stierstorfer, Jörg
Abstract: Highly energetic 1‐(azidomethyl)‐5 H ‐tetrazole (AzMT, 3 ) has been synthesized and characterized. This completes the series of 1‐(azidoalkyl)‐5 H ‐tetrazoles represented by 1‐(azidoethyl)‐5 H ‐tetrazole (AET) and 1‐(azidopropyl)‐5 H ‐tetrazole (APT). AzMT was thoroughly analyzed by single‐crystal X‐ray diffraction experiments, elemental analysis, IR spectroscopy and multinuclear ( 1 H, 13 C, 14 N, 15 N) NMR measurements. Several energetic coordination compounds (ECCs) of 3d metals (Mn, Fe, Cu, Zn) and silver in combination with anions such as (per)chlorate, mono‐ and dihydroxy‐trinitrophenolate were prepared, giving insight into the coordination behavior of AzMT as a ligand. The synthesized ECCs were also analyzed by X‐ray diffraction experiments, elemental analysis, and IR spectroscopy. Differential thermal analysis for all compounds was conducted, and the sensitivity towards external stimuli (impact, friction, and ESD) was measured. Due to the high enthalpy of formation of AzMT (+654.5 kJ mol −1 ), some of the resulting coordination compounds are extremely sensitive, yet are able to undergo deflagration‐to‐detonation transition (DDT) and initiate pentaerythritol tetranitrate (PETN). Therefore, they are to be ranked as primary explosives. Abstract : Shortening the alkyl chain in 1‐(Azidoethyl)‐5 H ‐tetrazole (AET) to a methylene bridge results in the formation of highly sensitive 1‐(azidomethyl)‐5 H ‐tetrazole (AzMT), which exhibits a greatly increased enthalpy of formation, hence a drastically increased detonation performance is calculated. Like AET, AzMT can be applied as ligand in the energetic coordination compounds (ECC) of several transition metals, showing the characteristics of primary explosives capable of initiating pentaerythritol tetranitrate. The ligand as well as all ECCs are fully characterized.